Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Hotel di Kabupaten Aceh Barat - Alisman Alisman (Syiah Kuala University, 2015)
This study aims at identifying and analyzing factors that affect tax revenues in aceh barat. data were used from 2006 to 2012. A multiple regression model was used. estimation results showed that the number of visitors and supply of hotel rooms have a positive and significant impact on tax revenue in aceh barat. revenue from hotel tax increased by Rp. 570 823 rupiah for each additional one room building units. hotel tax revenues also increased by Rp. 73 785 rupiah for each additional one visitor. based on these results, the local government have to provide facilities that can attract the private sector to increase the number of rooms. the local government is also expected to attract tourists by increasing the availability of tourist destinations that contribute to the increase in hotel tax revenues.